Does ego identity process have a predictive role in drug abstinence? - Teze, Saniye; Ayhan, Fatma (Journal of Dependence, 2023)
Objective: The aim of this study was to investigate the predictive effect of ego identity process on self-efficacy for abstinence from substance abuse. Method: The research that is descriptive and correlational was conducted with 415 young individuals between the dates 01.07.2021 and 30.01.2022. Socio-demographic characteristics information form, Ego Identity Process Questionnaire (EIPQ) and Self-Efficacy for Protecting Adolescences from Substance Abuse Scale (SEAPSAS) were applied in this study. Results: The general mean score of the youth sub-dimension of abstinence from substances/stimulants in the SEAPSAS scale was 54.13±11.05, and the total mean score of the EIPQ was 124.86±15.84. A moderate positive correlation was identified between the total scores of the EIPQ and SEAPSAS scales. Although the detected correlation coefficient was significant, EIPQ’s interpretation of SEAPSAS was at a low level (R2=.135). According to participants’ socio-demographic characteristics, the scores obtained from the SEAPSAS were low in males, those with a bachelor’s or higher education degree, those living in a dormitory or alone, those with six or more siblings, those with fragmented families, those who smoke, and in those who are children of working mothers. EIPQ stability sub-dimension score of the participants who live in the county is higher than those who live in the province. Conclusion: In line with the results of the study, it is recommended to organize programs that will develop the young’s ego identity process and self-efficacy for abstinence from substance abuse. It is expected that these programs will contribute to the prevention of substance addiction.